The Effect of Lavender Aromatherapy in Reducing Emesis Gravidarum in First Trimester Pregnant Women in The Working Area of Maracang Health Center, Purwakarta Regency - Mareta, Ewith Widya (Jurnal Indonesia Sosial Sains, 2025)
Pregnancy induces various physiological changes, including Emesis Gravidarum (nausea and vomiting), which predominantly affects first-trimester women and significantly reduces comfort. This research aimed to analyze the effect of lavender aromatherapy on reducing Emesis Gravidarum in first-trimester pregnant women in the working area of Babelan 1 Health Center, Bekasi City, in 2023. A pre-experimental, one-group pretest-posttest design was employed, with purposive sampling selecting 38 respondents. Data were collected using the PUQE-24 checklist and analyzed using the Wilcoxon and Chi-Square tests. The Wilcoxon test results indicated a significant reduction in Emesis Gravidarum after the lavender aromatherapy intervention (p-value = 0.000). Chi-Square analysis revealed that only parity was significantly associated with the incidence of Emesis Gravidarum (p-value = 0.010), while maternal age and occupation showed no significant relationship. The study concludes that lavender aromatherapy effectively reduces Emesis Gravidarum in first-trimester pregnant women. These findings support the integration of lavender aromatherapy as a non-pharmacological intervention in maternal healthcare services to improve the well-being of pregnant women experiencing nausea and vomiting.